Acts of naming : the family plot in fiction - Ragussis, Michael (Oxford University Press, 1986)
Michael Ragussis re-reads the novelistic tradition by arguing the acts of naming--bestowing, revealing, or earning a name; taking away, hiding, or prohibiting a name; slandering, or protecting and serving it--lie at the center of fictional plots from the 18th century to the present. Againstthe background of philosophic approaches to naming, Acts of Naming reveals the ways in which systems of naming are used to appropriate characters in novels as diverse as Clarissa, Fanny Hill, Oliver Twist, Pierre, Tess of the d'Urbervilles, Remembrance of Things Past, and Lolita, and identifiesunnaming and r.